2008
DOI: 10.2116/analsci.24.1279
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of 1-Decyl-3-methylimidazolium Bromide and Solvation Structure of Bromide at the Air/Water Interface

Abstract: The adsorbed film of 1-decyl-3-methylimidazolium bromide (DeMIMB) at the air/water interface was investigated employing the surface tension measurement and the x-ray absorption fine structure method under the total reflection condition (TRXAFS). From the surface tension measurement, the surface excess concentrations of ions were determined. From the XAFS measurement, two solvation states of bromide ion were found in the adsorbed film, which were assigned to be "free-Br" and "bound-Br". The hydration number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The ionic liquids based of 1-alkyl-3-methylimidazolium ion have been investigated recently as short-chain cationic surfactant in the field of colloid and interface science because the imidazolium cations have an amphiphilic structure and their assembled states is, at least partly, similar to structure of neat ionic liquids [7][8][9][10][11]. We have previously studied the surface property of the aqueous solutions of 1-hexyl-3-methylimidazolium tetrafluoroborate (HMIMBF 4 ) and a usual cationic surfactant with BF 4 as its counter anion, dodecyltrimethylammonium tetrafluoroborate (DTABF 4 ), by employing the surface thermodynamics and X ray absorption fine structure under total reflection condition (TRXAFS) [12,13]. It was demonstrated that for example, the surface pressure  vs. the average area per molecule A curve of the HMIMBF 4 system is almost vertical, which suggests an incompressible adsorbed film, at the saturation adsorption whereas those of DTABF 4 and dodecyltrimethylammonium bromide (DTAB) systems show a higher compressibility even at their saturation adsorption ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic liquids based of 1-alkyl-3-methylimidazolium ion have been investigated recently as short-chain cationic surfactant in the field of colloid and interface science because the imidazolium cations have an amphiphilic structure and their assembled states is, at least partly, similar to structure of neat ionic liquids [7][8][9][10][11]. We have previously studied the surface property of the aqueous solutions of 1-hexyl-3-methylimidazolium tetrafluoroborate (HMIMBF 4 ) and a usual cationic surfactant with BF 4 as its counter anion, dodecyltrimethylammonium tetrafluoroborate (DTABF 4 ), by employing the surface thermodynamics and X ray absorption fine structure under total reflection condition (TRXAFS) [12,13]. It was demonstrated that for example, the surface pressure  vs. the average area per molecule A curve of the HMIMBF 4 system is almost vertical, which suggests an incompressible adsorbed film, at the saturation adsorption whereas those of DTABF 4 and dodecyltrimethylammonium bromide (DTAB) systems show a higher compressibility even at their saturation adsorption ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, our previous studies demonstrated that for the pure solution of DTABF 4 , BF À 4 ions did not form side-by-side pairs with DTA + at the surface [37]. For the pure solution of DTABr, part of Br À ions bound with surfactant ions in the Stern layer, whereas the rest existed in the diffuse double layer in free-Br state [31,35,44]. Therefore, such segregation may not be expected or very weak even if it would happen for the DTABr-DTABF 4 mixture.…”
Section: Counterions Distributionmentioning
confidence: 92%
“…Room-temperature ionic liquids have been expected to become excellent alternatives to conventional solvents, electrolytes, and lubricants due to their special features. From the viewpoint of interfacial chemistry, almost all ionic liquids, especially those with long hydrocarbon chains, have amphiphilic structures . Ionic liquids are also attracting much attention as alternative surfactants to conventional oil dispersants in enhanced oil recovery processes because they are environmentally benign…”
Section: Introductionmentioning
confidence: 99%